2010
DOI: 10.1007/s12598-010-0038-y
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Na/K ratio on the phase structure and electrical properties of Na x K1−x NbO3 lead-free piezoelectric ceramics

Abstract: Lead-free piezoelectric Na x K 1-x NbO 3 (x = 0.3-0.8) (NKN) ceramics were fabricated by normal sintering at 1060°C for 2 h. Microstructures and electrical properties of the ceramics were investigated with a special emphasis on the influence of Na content. The grain size of the produced dense ceramic was decreased by increasing Na content. A discontinuous change in the space distance was found at the composition close to Na 0.7 K 0.3 NbO 3 ceramic, which indicates the presence of a transitional composition bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 18 publications
0
14
0
Order By: Relevance
“…Electrochemical parameters of as‐cast in comparison with heat treated specimens are presented in Table . The corrosion rate ( P i ) of samples obtained from the corrosion current density was calculated according to the following equation . Pi=22.85 icorr According to Equation , Mg–3Zn and heat treated alloys showed similar corrosion rate in the range of 4.81–5.21 mm/year.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Electrochemical parameters of as‐cast in comparison with heat treated specimens are presented in Table . The corrosion rate ( P i ) of samples obtained from the corrosion current density was calculated according to the following equation . Pi=22.85 icorr According to Equation , Mg–3Zn and heat treated alloys showed similar corrosion rate in the range of 4.81–5.21 mm/year.…”
Section: Resultsmentioning
confidence: 99%
“…However, Yang et al indicated that corrosion behaviour of binary Mg–Dy alloys were less significantly affected by heat treatment. Zhang et al also suggested that the corrosion rate of Mg–15Y alloy considerably increased after heat treatment. Studies on the effect of heat treatment on the corrosion resistance of AZ91D, Mg–Y and Mg–Dy alloys had been widely reported .…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Previously, it was found that the K/Na ratio and the Na contents can also affect electrical performance of KNN -based materials [14,15]. Table 1 lists the relationships between piezoelectric properties and phase boundary of KNN -based ceramics [6,[9][10][11][12][13][14][15]. It shows that the piezoelectric properties of KNN -based materials strongly depend on the type of phase boundaries, and the rhombohedral-tetragonal (R-T) phase boundary plays a dominant role on their piezoelectricity.…”
Section: Introductionmentioning
confidence: 99%
“…The higher Na-K ratio in the 300-µm fibers seen from EDX and XRD resulted in samples with lower deformation, as suggested by Zhao et al [32], though unlike Zhao et al, the effect observed with the grain size resembled that of Zhang et al, whereby with an increasing Na-K ratio, the grain size decreased [39], and the effect on Pr was more related to the effect seen in Du et al, where an optimum ratio of 54:46 of Na-K was found, after which any increase in the ratio led to a decrease in the Pr [40]. The differing hypotheses from the various groups suggest that the results improve to a certain optimum where the greatest amount of phases exist, i.e., MPT, and then decrease, as was seen in Du et al, as the alkali content moves away from the MPT.…”
Section: Electromechanical Investigationmentioning
confidence: 58%